How Much Is Prevention Worth? - Mueller, Hannes (World Bank, Washington, DC, 2018)
The goal of this report is to present the results from a unified conceptual framework so as to evaluate the cost-effectiveness and different trade-offs involved in conflict prevention. The context for the framework’s development is a radical rethinking of the peacebuilding architecture put forth by several reports published in 2015. One of these reports, an expert report that formed part of the review of the United Nations’ peacebuilding architecture, argued for shifting away from a narrow understanding of peacebuilding—where the aim is to avoid relapsing into violent conflict—toward an understanding that sustains peace. If this advice is heeded, the World Bank and the United Nations will need to leave behind the predominantly postconflict focus of peacebuilding and reimagine it as a more comprehensive enterprise where prevention is also included.